SIMULASI METODE BACK PROPAGATION DALAM ANALISIS KERUSAKAN RUAS JALAN LINTAS UTARA KOTA PEKANBARU - Alfian Saleh; Muthia Anggraini; Roki Hardianto (LPPM Universitas Abdurrab, 2023)
The Pekanbaru City North Cross Road is a national road connects the city of Pekanbaru with the northern border of Pekanbaru which is a causeway often damaged. So we need a system to predict the damage that occurs. This research method consists of data collection, data selection, the process using the backpropagation method, analysis, and evaluation. Based on the data obtained the most damage that occurs on this road segment is 60% cracking, 30% rutting damage, and 10% for potholes. Backpropagation are weight initiation, activation, calculating input weights, output bias, and changes in weight. In these stages, the output to be achieved is obtained with the smallest error approach.. The result is that the prediction of damage made there is an increase in the number of crack damage by about 3% with an MSE error value of 0.18535 with Matlab software